IMPACT OF THE NORMS OF MINERAL FERTILIZERS ON THE BUCKWHEAT DENSITY, DURATION OF VEGETATION AND PRODUCTIVITY UNDER CONDITIONS OF THE WESTERN FOREST-STEPPE - Dykyi, О. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
Buckwheat is proved to be a vital granular crop with high content of protein, oil, carbohydrate, iron, calcium, phosphorus, etc. It contains rutin, which is important for physiological activity of human organism. Buckwheat is a good agro technical precursor for winter and spring grain crops. Buckwheat cultivation promotes development of beekeeping in Ukraine. Buckwheat can be grown in repeated crops. The article presents a brief review of researches and scientific publications, which confirm importance and relevance of the mentioned problem both in Ukraine and abroad. The research highlights findings of three years of examining mineral fertilizers influence on buckwheat density, duration of vegetation, elements of structure and fertility. The experiments belong to the 2-factors research on the experimental fields of the Department of Crop Growing Technologies with application of P40K40 + N40 (additional fertilizing), P60K60 + N60 (additional fertilizing), P20K20N20 (additional fertilizing). It was determined that the largest plant density at the time of harvesting (236.6 p/м2) under the longest vegetation period (104 days) was secured by the variant of fertilizers application at the norm P60K60 +N60 (additional fertilization). Application of nitrogen in pre-sowing cultivation provokes increase of the number of brunches of the first order (pieces per plant), a number (p) of racemes and flowers. Application of higher norms of mineral fertilizers and nitrogen in additional fertilization during the period of blooming causes increase of such elements of structure as the number (p) and mass (r) of grains of full value. The largest values of these indices were fixed in the variant P60K60+N60 (additional fertilization) – 41.23; 1.15; 28.00 respectively. Such combination of the structure elements provided the highest level of harvest. For the three years of the research, that average yield was 2.49 t/ha.